THE EFFECT OF COMPETENCE, WORK ETHIC, AND TEAMWORK ON EMPLOYEE PERFORMANCE AT THE BATAM CITY POPULATION AND CIVIL REGISTRATION OFFICE - Rasyid Hidayat Sagala; Mira Yona; Habibuddin Nasution; Amanda Lyanfitri (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This research aims to examine how competence, work ethic, and teamwork influence employee performance at the Population and Civil Registration Office of Batam City. A quantitative explanatory approach was applied, involving the entire workforce of the institution as respondents through a census method (n = 80). Data were gathered using a Likert-scale questionnaire (1–5) developed from the dimensions of competence, work ethic, teamwork, and performance. Prior to analysis, the instrument underwent validity and reliability testing, where all items were confirmed valid, and Cronbach’s Alpha values ranged between 0.86 and 0.90, indicating strong internal consistency. The analytical process consisted of descriptive statistics, classical assumption tests (normality, multicollinearity, and heteroskedasticity), and multiple linear regression to evaluate both partial and simultaneous relationships among variables. Descriptive findings revealed that competence (mean = 4.05), work ethic (mean = 4.12), teamwork (mean = 4.18), and performance (mean = 4.08) were categorized as high. Regression analysis demonstrated that competence (β = 0.28; p = 0.002), work ethic (β = 0.31; p = 0.000), and teamwork (β = 0.26; p = 0.004) each exerted a positive and significant influence on performance. Collectively, the three variables had a significant joint effect, with an F-value of 32.45; p = 0.000 and an R² of 0.58, signifying that 58% of employee performance variation was explained by these factors. The results suggest that enhancing employee performance at the Population and Civil Registration Office requires an integrated strategy focused on strengthening competence, cultivating a strong work ethic, and fostering teamwork.